التدوين المبكر للسنة دراسة في الحجية والمناهج - Abdullah, I.; Abdul Manas, S. (Universiti Sains Islam Malaysia, 2024)
This research presents the steps of writing the Sunnah in the Prophet's era, in the historical evidence and evidence market, indicating the effect of proving early writing in the process of protesting the Sunnah, and responding to appeals - which were old and new to the protest process - based on some accounts in which the prohibition was mentioned with the writing of the hadith In the difficulty of the message, and to take that as an excuse to challenge the integrity of the blogging that took place during the reign of Caliph Omar bin Abdul Aziz. The research also shows the effect of the modern blogs written in the first half of the second century AH on the curricula of the modernists in the following eras, and the effect of those blogs on the curricula of the jurists as well, especially the blogs of Hassan Basri, Al-Kalaei and Zaid bin Ali, which were developed in a very early period.